2012
DOI: 10.3390/rs4051232
|View full text |Cite
|
Sign up to set email alerts
|

Improving Landslide Forecasting Using ASCAT-Derived Soil Moisture Data: A Case Study of the Torgiovannetto Landslide in Central Italy

Abstract: Predicting the spatial and temporal occurrence of rainfall triggered landslides represents an important scientific and operational issue due to the high threat that they pose to human life and property. This study investigates the relationship between rainfall, soil moisture conditions and landslide movement by using recorded movements of a rock slope located in central Italy, the Torgiovannetto landslide. This landslide is a very large rock slide, threatening county and state roads. Data acquired by a network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 40 publications
3
66
0
1
Order By: Relevance
“…Specifically, in Brocca et al (2013) the model was validated exactly in the same study area by obtaining reliable and satisfactory results. Based on previous studies, the accuracy (RMSE) of SWBM was found to range between 0.02 and 0.04 m 3 m −3 when compared with in situ measurements.…”
Section: Soil Water Balance Modelmentioning
confidence: 99%
“…Specifically, in Brocca et al (2013) the model was validated exactly in the same study area by obtaining reliable and satisfactory results. Based on previous studies, the accuracy (RMSE) of SWBM was found to range between 0.02 and 0.04 m 3 m −3 when compared with in situ measurements.…”
Section: Soil Water Balance Modelmentioning
confidence: 99%
“…Similarly, a limited number of stations can be used for the validation of coarse scale satellite soil moisture products, as indirectly demonstrated by the high correlations that are frequently obtained between coarse scale (~20 km) and point scale (~5 cm) measurements (e.g., [57][58][59]). Vice versa, coarse scale measurements, as obtained by remote sensing, can be used for regional or local studies (e.g., [11,86]). In summary, the temporal stability concept allows to mitigate the spatial discrepancies between point measurements and the scale needed in the applications.…”
Section: How Does the Soil Moisture Vary In Space And Time?mentioning
confidence: 99%
“…Soil moisture governs the partitioning of the mass and energy fluxes between the land and the atmosphere, thus playing a key role in the assessment of the different components of the water and energy balance. Soil moisture is an important variable for flood and landslide modelling and prediction [9][10][11][12], for drought assessment and forecasting [13][14][15], and for numerical weather prediction [16][17][18][19], to cite a few. Soil moisture is also the water source for plants and, hence, its knowledge is required for irrigation management and agricultural studies [20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of observations from satellites has become a powerful tool to enhance our understanding of the role of soil moisture in the hydrological cycle in a number of areas, e.g., land-atmosphere processes (Miralles et al, 2012;Taylor et al, 2012); weather and runoff forecasts (Brocca et al, 2010;Bisselink et al, 2011); landslides (Brocca et al, 2012b); and rainfall products (Chen et al, 2012). Since 2000 several satellite missions measuring soil moisture have been launched: e.g., the Advanced Microwave Sounding Radiometer for EOS (AMSR-E) (Njoku and Chan, 2006), the Advanced SCATterometer (ASCAT) (Bartalis et al, 2007b), and the Soil Moisture Ocean Salinity (SMOS) .…”
Section: Introductionmentioning
confidence: 99%